2018
DOI: 10.48550/arxiv.1812.05189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Massively scalable Sinkhorn distances via the Nyström method

Abstract: The Sinkhorn "distance," a variant of the Wasserstein distance with entropic regularization, is an increasingly popular tool in machine learning and statistical inference. However, the time and memory requirements of standard algorithms for computing this distance grow quadratically with the size of the data, making them prohibitively expensive on massive data sets. In this work, we show that this challenge is surprisingly easy to circumvent: combining two simple techniques-the Nyström method and Sinkhorn scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…Its increasing popularity in machine learning follows from the landmark paper [Cut13], who showed that it defines a differentiable loss function for supervised learning, and takes advantage of GPU architectures. We also refer to [BCC + 15,ABRW18] for some illustrative recent works presenting theoretical and numerical advances on Sinkhorn's algorithm.…”
Section: Entropic Regularizationmentioning
confidence: 99%
“…Its increasing popularity in machine learning follows from the landmark paper [Cut13], who showed that it defines a differentiable loss function for supervised learning, and takes advantage of GPU architectures. We also refer to [BCC + 15,ABRW18] for some illustrative recent works presenting theoretical and numerical advances on Sinkhorn's algorithm.…”
Section: Entropic Regularizationmentioning
confidence: 99%
“…Conventionally, to compute with such data one might begin by extracting a low-dimensional representation using nonlinear dimensionality reduction ("manifold learning") algorithms [3-5, 7, 15, 54, 55]. For supervised tasks, there is also theoretical work on kernel regression over manifolds [12,14,22,51]. These results rely on very general Sobolev embedding theorems, which are not precise enough to specify the interplay between regularity of the kernel and properties of the data need to obtain concrete resource tradeoffs in the two curve problem.…”
Section: Related Workmentioning
confidence: 99%
“…This regularization allows the computation of OT for large problems, such as those arising in machine learning [14,22,23] or computer graphics [7,42,44]. Recently, Altschuler et al [2] introduced a method to accelerate the Sinkhorn algorithm via low-rank (Nyström) approximations of the kernel [2]. Simultaneously, there have been considerable efforts to study the convergence and approximation properties of the Sinkhorn algorithm [3] and its variances [21].…”
Section: Computational Optimal Transportmentioning
confidence: 99%